Fault characteristic of a power transformer in Bangladesh power grid - Kabir, Md Arifur; Alam, Mohammad Khurshed; Chowdhury, Abdul Hasib (Institute of Electrical and Electronics Engineers Inc., 2020)
Faults in an electric power system hinder the sustainability and longevity of power system components. Protective devices should be well coordinated for rapid removal of fault. Transformers are expensive and critical equipment and requires full-fledge protection to ensure operational reliability. Grid transformer failure may result in a brownout of an area. This paper focuses on a power transformer fault that occurred in the Bangladesh power grid, analyses characteristics of the fault, and suggests modifications to the existing protection scheme.